A river enchanted : a novel - Ross, Rebecca (Rebecca J.) (New York, NY : Harper Voyager, an imprint of HarperCollins Publishers, 2022)
Jack Tamerlaine hasn't stepped foot on Cadence in ten long years, content to study music at the mainland university. But when young girls start disappearing from the isle, Jack is summoned home to help find them. Enchantments run deep on Cadence: gossip is carried by the wind, plaid shawls can be as strong as armor, and the smallest cut of a knife can instill fathomless fear. The capricious spirits that rule the isle by fire, water, earth, and wind find mirth in the lives of the humans who call the land home. Adaira, heiress of the east and Jack's childhood enemy, knows the spirits only answer to a bard's music, and she hopes Jack can draw them forth by song, enticing them to return the missing girls. --
Includes bibliographical references (pages 466-467).
Keywords: Musicians -- Fiction; Secrecy -- Fiction; Missing persons -- Fiction; Girls -- Fiction; Spirits -- Fiction; Songs -- Fiction; Partnership -- Fiction; Imaginary places -- Fiction; Fantasy fiction; Romance fiction